BRAT1 encephalopathy: a recessive cause of epilepsy of infancy with migrating focal seizures. (23rd December 2019) - Scheffer, Ingrid E; Boysen, Katja E; Schneider, Amy L; Myers, Candace T; Mehaffey, Michele G; Rochtus, Anne M; Yuen, Yuet‐Ping; Ronen, Gabriel M; Chak, Wai Km; Gill, Deepak; Poduri, Annapurna; Mefford, Heather C
Abstract : Epilepsy of infancy with migrating focal seizures (EIMFS), one of the most severe developmental and epileptic encephalopathy syndromes, is characterized by seizures that migrate from one hemisphere to the other. EIMFS is genetically heterogeneous with 33 genes. We report five patients with EIMFS caused by recessive BRAT1 variants, identified via next generation sequencing. Recessive pathogenic variants in BRAT1 cause the rigidity and multifocal seizure syndrome, lethal neonatal with hypertonia, microcephaly, and intractable multifocal seizures. The epileptology of BRAT1 encephalopathy has not been well described. All five patients were profoundly impaired with seizure onset in the first week of life and focal seizure migration between hemispheres. We show that BRAT1 is an important recessive cause of EIMFS with onset in the first week of life, profound impairment, and early death. Early recognition of this genetic aetiology will inform management and reproductive counselling. What this paper adds: Recessive BRAT1 pathogenic variants cause epilepsy of infancy with migrating focal seizures (EIMFS). BRAT1 EIMFS has seizure onset in the first week of life and profound impairment. This article is commented on by Guerrini on page 1012 of this issue.